An ultra-cold cement-based porous radiation refrigeration filler and a preparation method thereof

CN122941228APending Publication Date: 2026-10-20JIANGXI YINSHAN SUPER MATERIAL TECH CO LTD
View PDF 2 Cites 0 Cited by

Patent Information

Application Number
CN202611096198.7
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2026-07-23
Publication Date
2026-10-20

AI Technical Summary

Technical Problem

本发明要解决的技术问题包括:现有水泥基辐射制冷填料因原料比表面积不足导致水化反应不充分、显色杂质残留、白度偏低的问题;传统水泥基多孔材料依赖化学发泡剂、致孔剂造孔导致粉体白度下降、生产成本增加、环保压力大的问题;水泥行业长期固守低水灰比配方的技术偏见,尚无利用超高水灰比体系进行原位造孔制备功能填料粉体的技术先例;常规静置水化过程中浆体抱团结块、水分分布不均、孔隙结构无序的问题;现有水泥基辐射制冷填料制备过程中缺乏适配高水灰比体系的活化配伍方案、水化产物结构致密、光散射效应微弱的问题

Benefits of technology

第一,填料白度等级高,粉体光学均匀一致性优异。本发明通过高活性超冷水泥(比表面积≥700 m2/kg)的完全水化反应消解显色矿物组分、定量碱激发加速有色杂质溶出析出、梯度高温烘干消除晶格色心缺陷等多重手段协同作用,再叠加内部微孔结构形成的强可见光散射增白效应,可将水泥原料94以上的初始亨特白度稳定提升至96以上,成品粉体色相纯净统一,无杂色偏差。高比表面积水泥粉体提供了充足的反应活性位点,使熟料矿物水化转化率达到95%以上,从根源上消除了未水化含铁熟料残渣的显色贡献;碱激发环境促进了水化产物晶体在溶液中的均匀成核与生长,同时加速了游离碱溶性有色杂质的溶出;高温烘干过程中晶格内部氢氧根空位和低价铁离子色心缺陷被有效消除,进一步提升了粉体的光学纯净度。

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure FT_1
    Figure FT_1
  • Figure FT_2
    Figure FT_2
  • Figure SMS_1
    Figure SMS_1
Patent Text Reader

Abstract

This invention discloses an ultracold cement-based porous radiation cooling filler and its preparation method, belonging to the field of cement-based new materials technology. Addressing the problems of low whiteness, reliance on chemical pore-forming agents, and high preparation costs of existing radiation cooling fillers, the filler of this invention is prepared from ultracold cement, an alkali activator, and water, wherein the ultracold cement powder has a specific surface area ≥700 m². 2 / kg, Hunter whiteness > 94 degrees, iron oxide content ≤ 0.2%wt, the amount of alkali activator added is 2% to 6% of the total mass of the ultra-cold cement powder, and the water-cement ratio of the water to the ultra-cold cement is 3.0 to 4.0. This invention requires no addition of any chemical foaming agents or pore-forming agents throughout the entire process. It relies on the natural evaporation of free water within the ultra-high water-cement ratio system to create pores in situ. The product has excellent performance and can be widely used in fields such as building energy-saving coatings, outdoor equipment cooling coatings, and photovoltaic backsheet heat dissipation and protection coatings.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] This invention belongs to the field of cement-based new materials technology, specifically relating to a radiative cooling functional filler and its preparation method, and particularly to a porous radiative cooling filler prepared by an in-situ pore-forming process using ultra-cold cement as a matrix and an ultra-high water-cement ratio. It can be widely used in fields such as building energy-saving coatings, passive cooling coatings for outdoor equipment, roof thermal insulation materials, and photovoltaic backsheet heat dissipation and protection coatings. Background Technology

[0002] Radiative cooling is a passive cooling technology that achieves self-heating and cooling without external energy input, relying on the spectral properties of the material itself. Its core principle lies in the material's surface possessing high reflectivity in the solar spectrum (0.25–2.5 μm) to minimize heat absorption from the outside world, while simultaneously exhibiting high infrared emissivity in the atmospheric window spectrum (8–13 μm) to effectively radiate its own heat into outer space through atmospheric transparency. With the rapid development of building energy conservation, passive cooling of outdoor equipment, and urban heat island management, radiative cooling materials have become a key research area in the industry.

[0003] Currently, the mainstream inorganic fillers for radiation cooling on the market mainly include rutile titanium dioxide, precipitated barium sulfate, and heavy calcium carbonate. For example, CN117567878B discloses a high-performance porous radiation cooling filler and its preparation method, using silicon oxide, titanium oxide, and rare earth oxides as raw materials, and preparing porous fillers through processes such as ball milling, sintering, quenching, and combining with graphite slurry composite and high-temperature treatment. Although this type of solution can achieve certain radiation cooling performance, it has the following significant drawbacks: First, the procurement cost of raw materials such as titanium oxide and rare earth oxides is high, which restricts the large-scale promotion and application of the product; second, the preparation process involves high-temperature sintering (usually above 1000℃) and quenching processes, which consume a lot of energy, require high-end equipment, and have a long production cycle; third, this type of inorganic oxide filler has poor weather resistance during long-term outdoor use and is prone to performance degradation problems such as powdering and discoloration.

[0004] CN115466086A discloses a cement-based passive cooling composite material and its preparation method. The composite material is prepared using white cement, white silica fume, limestone powder, and rutile titanium dioxide powder as raw materials through casting molding, sealed curing, and high-temperature autoclaving. While this method introduces a cement matrix to reduce some costs, it still relies on high-cost functional fillers such as rutile titanium dioxide. Furthermore, the water-cement ratio is only 0.25–0.45, and the traditional casting molding process results in a dense internal structure, making it difficult to form a multi-level microporous structure conducive to light scattering, thus limiting the potential for improving radiative cooling performance.

[0005] CN121990801A discloses a porous microstructured foamed white cement radiation cooling composite material and its preparation method, using sulfoaluminate white cement as the base material and forming a porous microstructure by adding a foaming agent. Although this method utilizes the porous structure to enhance scattering, the pore-forming process relies on chemical foaming agents. Foaming agent residues can significantly reduce the Hunter whiteness of the powder, damage optical purity, and increase production costs and environmental pressure.

[0006] A team led by Academician Miao Changwen from Southeast University reported a "supercold cement" in *Science Advances*. Starting from the clinker composition, through the synergistic control of the selection of underlying materials and surface structure design, this self-cooling cement can achieve high reflectivity and high infrared emissivity without any additives. CN120004577A (Southeast University) further discloses a radiation-cooled cement-based material with a metasurface. The mass ratio of cementitious material particles:water:admixture is (1-2):(0.4-0.6):(0.01-0.02), i.e., the water-cement ratio is only 0.4-0.6. By using a template method and a pressure gradient-driven gas volume expansion method, the spontaneous arrangement and growth of bubbles are guided on the surface of the cement-based material slurry to obtain the metasurface cement-based material. Although the aforementioned "ultra-cold cement" series of technologies achieves excellent radiative cooling performance without the need for additives, its core lies in the nano-engineering modification through cavitation strategies, the construction of self-assembled reflective crystals and multi-level porous structures. The product form is a block cement material rather than a powder filler, and it does not involve in-situ pore-forming technology under ultra-high water-cement ratio systems.

[0007] Furthermore, existing alkali-activated cement-based porous materials, such as alkali-activated porous cement-based thermal insulation materials, utilize alkali activation reactions, silicate hydrothermal reactions, and gas evolution changes to form porous structures. However, their core purpose is to improve the mechanical strength and durability of the thermal insulation material, and pore formation still relies on gas evolution reactions, rather than the in-situ pore formation through the evaporation of free water at ultra-high water-cement ratios as described in this invention. Although the solid waste-based geopolymer radiation cooling coating utilizes alkali-activated gelation activity to prepare the coating, it belongs to a geopolymer system, which is fundamentally different from the cement hydration system, and also does not involve ultra-high water-cement ratio flow dynamic hydration processes.

[0008] In summary, existing radiation-cooled filler technologies struggle to simultaneously achieve high whiteness, high porosity, low cost, and green preparation. There is an urgent need for a novel technical solution based on precise selection of highly active raw materials, quantitative alkali activation for synergistic activation, complete elimination of chemical pore-forming agents, and breakthroughs in traditional solidification processes. Summary of the Invention

[0009] To address the shortcomings of the existing technologies, this invention provides an ultracold cement-based porous radiation cooling filler and its preparation method. The technical problems this invention aims to solve include: insufficient hydration reaction, residual coloring impurities, and low whiteness in existing cement-based radiation cooling fillers due to insufficient specific surface area of ​​raw materials; the reliance on chemical foaming agents and pore-forming agents in traditional cement-based porous materials, leading to decreased powder whiteness, increased production costs, and significant environmental pressure; the long-standing technical bias in the cement industry towards low water-cement ratio formulations, with no precedent for using ultra-high water-cement ratio systems for in-situ pore-forming preparation of functional filler powders; problems such as slurry agglomeration, uneven moisture distribution, and disordered pore structure during conventional static hydration; and the lack of activation and compatibility schemes suitable for high water-cement ratio systems, resulting in dense hydration product structures and weak light scattering effects in the preparation of existing cement-based radiation cooling fillers.

[0010] To achieve the above objectives, the present invention provides the following technical solution: an ultracold cement-based porous radiation cooling filler, prepared from ultracold cement, an alkali activator, and water, wherein the powder specific surface area of ​​the ultracold cement is ≥700 m². 2 / kg, Hunter whiteness > 94 degrees, iron oxide content ≤ 0.2%wt, the amount of alkali activator added is 2% to 6% of the total mass of the ultracold cement dry powder, and the water-cement ratio of the water to the ultracold cement is 3.0 to 4.0.

[0011] Further preferably, the amount of alkali activator added is 4% of the total mass of the ultracold cement dry powder.

[0012] Further preferably, the ultracold cement is white silicate cement or white sulfoaluminate cement, with a specific surface area of ​​700–900 m². 2 / kg, Hunter Whiteness is 94-97 degrees.

[0013] More preferably, the alkaline activator is selected from any one of sodium silicate, calcium hydroxide, and potassium hydroxide, or a compound mixture of the above components.

[0014] More preferably, the alkaline activator is a mixture of sodium silicate and calcium hydroxide in a mass ratio of (1-3):1.

[0015] Further preferably, the water-cement ratio is 3.2 to 3.8.

[0016] This invention strictly limits the specific surface area of ​​ultracold cement to 700 m². 2The water-cement ratio is above / kg, ensuring that cement particles have sufficient reactive sites, enabling clinker minerals to achieve a high conversion rate of over 95% during hydration, thereby eliminating the adverse effects of unhydrated iron-containing clinker residue on powder whiteness at its source. The addition of alkali activator not only accelerates the cement hydration reaction process, but more importantly, promotes the uniform nucleation and growth of hydration product crystals in solution, while providing an alkaline environment to accelerate the dissolution of free alkali-soluble colored impurities. The ultra-high water-cement ratio design of 3.0–4.0 breaks through the technical bias of traditional low water-cement ratios (usually 0.4–0.6) in the cement industry, providing sufficient free water as a "liquid template" for subsequent pore formation. This allows hydration products to grow in a suspended and dispersed state in an excess water environment, with free water uniformly filling the spaces between crystals and gel layers, laying the structural foundation for subsequent in-situ dehydration and pore formation.

[0017] When the amount of alkali activator added is 4%, the alkalinity environment of the system reaches the optimal balance point: it is sufficient to fully activate the hydration reaction of cement clinker minerals and accelerate the dissolution of colored impurities, while avoiding the formation of soluble salt residues in the subsequent drying process due to excessive introduction of alkali metal ions, thereby maximizing the optical purity of the powder while ensuring a high hydration reaction rate.

[0018] This invention also provides a method for preparing ultracold cement-based porous radiation cooling packing, comprising the following steps: Step 1: Raw material screening and pretreatment. Select raw materials with a specific surface area ≥700 m². 2 Ultra-cold cement with a weight of / kg, Hunter whiteness >94 degrees, and iron oxide content ≤0.2%wt is sieved (preferably using a 200-mesh standard inspection sieve) to remove large agglomerates and hard inorganic impurities from the raw material, ensuring that the overall particle size of the cement powder is uniform. After sieving, the cement powder is sealed for later use.

[0019] Step 2: Uniform activation and compounding of dry powder. The sieved ultracold cement powder is added to a dry powder mixing and stirring device. Alkali activator is weighed at a ratio of 2%–6% (preferably 4%) of the total mass of the ultracold cement powder and simultaneously added to the mixing device. The mixture is stirred (preferably at low speed for 5–10 minutes) to ensure uniform blending and fusion of the alkali activator and cement powder, thus completing the pre-activation treatment of the composite cement powder.

[0020] Step 3: Preparation of ultra-high water-cement ratio flowable cement slurry. At a water-cement ratio of 3.0–4.0, the pre-activated composite cement powder and water (preferably deionized water) are sequentially added to the mixing and reaction equipment. After all materials are added, the mixing equipment is immediately turned on for continuous, uninterrupted mixing throughout the process. This ensures the mixed cement slurry remains in a uniform, flowing, and suspended state. Strict control of the slurry state is maintained to prevent agglomeration, clumping, and solidification, thus constructing a stable fluid hydration reaction system.

[0021] Step Four: Constant Temperature Flow Dynamic Hydration Reaction. The mixing equipment containing the flow dynamic cement slurry is placed in a constant temperature curing environment of 25–40℃, and hydrated for 7–14 days with continuous mixing. The preferred constant temperature curing temperature is 30–35℃, and the curing time is 10–12 days. Under the synergistic activation of highly active cement powder and a quantitative alkali activator, the overall hydration conversion rate of various clinker minerals such as calcium sulfoaluminate and calcium silicate inside the cement reaches over 95%. A large amount of high-purity, stable hydration products such as ettringite, monosulfide hydrated calcium sulfoaluminate, hydrated calcium silicate gel, and calcium hydroxide are generated within the system. Excess free water in the slurry system is evenly distributed and fills the intercrystalline gaps, gel layers, and particle gaps of the hydration products. Simultaneously, the flow dynamic hydration system can fully dissolve free alkaline salts and various trace soluble colored impurities within the system, completing the chemical purification treatment of the filler matrix.

[0022] Step 5: Gradient-segmented high-temperature drying to solidify the microporous structure. The fluid cement slurry, having undergone sufficient hydration at a constant temperature, is left to stand to drain excess free water from the surface. The loose hydrated material is then broken into small pieces. A two-stage gradient drying process is used to complete the dehydration and shaping: the first stage is a low-temperature pre-drying stage, where the oven temperature is controlled at 60–80℃ and dried continuously for 2–4 hours to quickly remove free moisture adhering to the material surface; the second stage is a high-temperature deep drying stage, where the temperature is gradually increased to 150–200℃ and dried continuously at a constant temperature for 6–12 hours, with the preferred drying temperature being 180–200℃, to thoroughly remove capillary-bound water and gel-adsorbed water from the material's interior. After the moisture inside the system is completely removed, the space originally occupied by the moisture is permanently retained, naturally forming a stable hierarchical microporous structure. At the same time, the high-temperature drying environment can effectively eliminate hydroxide vacancies and low-valence iron ion lattice color center defects inside the hydration product lattice, eliminate the undesirable yellow and gray background color of the powder, and stabilize the ultra-high whiteness matrix structure of the filler.

[0023] Step Six: Ultrafine Grinding and Air Classification Purification. The hydrated solid material, after gradient high-temperature drying and possessing a uniform microporous structure, is fed into an ultrafine ball mill for ultrafine grinding. The powder particle size is controlled at 1500 mesh or higher, preferably 1800–2000 mesh. After grinding, an air classification system is used for sieving and purification to remove dense, non-porous coarse particles and various impurities. This process fully dissociates individual hydrated crystals with their own microporous structures, ultimately forming a dual visible light scattering system combining the micropores within the particles and the gaps between powder particles.

[0024] Step 7: Testing and Packaging. The finished radiation refrigeration packing material, after graded purification, is tested sequentially for various core performance indicators, including Hunter whiteness, bulk density, internal porosity, solar reflectivity, and atmospheric window emissivity. Once all indicators meet the standards, it is packaged using a moisture-proof and sealed method and then stored in a classified warehouse.

[0025] High specific surface area raw materials provide ample chemical driving force for subsequent processes; alkali-activated pre-activation transforms the high reactivity of the raw materials into an actual increase in hydration rate; ultra-high water-cement ratio provides the material basis for pore formation, while continuous dynamic stirring ensures the uniformity of the pore formation process; gradient high-temperature drying permanently solidifies the space occupied by liquid water into solid micropores; ultrafine grinding and air classification dissociate large porous bodies into individual filler particles with microporous structures, while removing dense impurities. Single process methods can only achieve small improvements in the single performance of the filler, while the multi-process synergistic combination design of this invention can simultaneously achieve multiple technical effects such as system impurity removal and purification to improve whiteness, in-situ construction of regular micropores to enhance light scattering, and optimization of the hydrated phase structure to improve infrared radiation performance.

[0026] A constant curing temperature of 30–35℃ provides a suitable thermodynamic driving force for the cement hydration reaction, significantly accelerating the hydration rate and shortening the curing cycle, while preventing excessively high temperatures from causing crystal transformation or coarsening of the hydration products. This ensures the high whiteness and uniformity of the microporous structure of the hydration products. A curing time of 10–12 days ensures that high specific surface area cement achieves a clinker mineral hydration conversion rate of over 95% under the synergistic effect of alkali activation.

[0027] The optimal high-temperature deep drying temperature is further selected as 180–200°C. This temperature range ensures that the defects of hydroxide vacancies and low-valence iron ion color centers inside the crystal lattice are fully eliminated, while avoiding excessively high temperatures that could lead to dehydroxylation or phase transformation of the hydration products (such as the dehydration and structural damage of ettringite above about 200°C). This achieves the best balance between eliminating defects and whitening, and maintaining the infrared-radiative active phase of the hydration products.

[0028] Grinding powder to an ultrafine particle size range of 1800–2000 mesh serves two purposes: firstly, it fully dissociates individual hydrated crystals, exposing the uniform microporous structure within the particles and maximizing the micropore scattering effect; secondly, the particle size within this range is on the same order of magnitude as the wavelength of visible light, and the inter-particle voids and internal micropores together constitute a dual light scattering system, further enhancing the powder's ability to diffusely reflect sunlight. Excessively coarse grinding fails to fully dissociate the microporous structure, while excessively fine grinding may damage some micropore walls and increase processing costs; 1800–2000 mesh represents the optimal range for overall performance.

[0029] Compared with the prior art, the present invention has the following advantages: First, the filler has a high whiteness grade and excellent optical uniformity of the powder. This invention utilizes highly active ultracold cement (specific surface area ≥700 m²). 2 The cement powder exhibits a synergistic effect, combining multiple methods such as complete hydration reaction to eliminate colored mineral components, quantitative alkali activation to accelerate the dissolution and precipitation of colored impurities, and gradient high-temperature drying to eliminate lattice color center defects. This, coupled with the strong visible light scattering whitening effect created by the internal microporous structure, can stably increase the initial Hunter whiteness of cement raw materials from above 94 to above 96. The finished powder has a pure and uniform hue, free from impurities. The high specific surface area of ​​the cement powder provides ample reactive sites, enabling a clinker mineral hydration conversion rate of over 95%, fundamentally eliminating the color contribution of unhydrated iron-containing clinker residue. The alkali-activated environment promotes the uniform nucleation and growth of hydration product crystals in solution, while accelerating the dissolution of free alkali-soluble colored impurities. During high-temperature drying, hydroxyl vacancies and low-valence iron ion color center defects within the crystal lattice are effectively eliminated, further enhancing the optical purity of the powder.

[0030] Secondly, the microporous structure is well-formed and controllable, with significant advantages in green and impurity-free pore-forming. This invention requires no addition of foaming agents, organic pore-forming agents, or any other chemical additives throughout the entire process, making the production process green and environmentally friendly, with no foreign impurities affecting powder performance. Utilizing an ultra-high water-cement ratio of 3.0–4.0 combined with a fluid dynamic hydration process, free water is evenly distributed between the crystal gaps and gel layer of the hydration products. After dehydration, uniformly graded micropores in the 20–500 nm range are formed in situ, significantly improving the powder's diffuse reflection capability of sunlight.

[0031] Third, the passive radiative cooling application performance is excellent. The stable phases such as hydrated calcium aluminate and hydrated calcium silicate gel generated during cement hydration have intrinsically high emissivity in the atmospheric transparency window range of 8-13μm. Combined with the strong scattering effect of sunlight by the multi-level microporous structure inside the powder, the filler prepared by this invention can simultaneously achieve the dual core performance of solar reflectivity ≥96% and atmospheric window emissivity ≥0.95. The actual passive cooling effect is comprehensively superior to traditional titanium dioxide and ordinary white cement-based cooling fillers.

[0032] Fourth, the all-inorganic matrix structure is stable, and its long-term outdoor weather resistance is extremely strong. The finished radiative cooling filler is a pure inorganic mineral hydration stable system with stable and reliable chemical properties. It has multiple advantages such as high temperature resistance, UV aging resistance, and resistance to rainwater and acid and alkali corrosion. It is not prone to yellowing, powdering, or performance degradation during long-term outdoor use, and its overall service life far exceeds that of various polymer-based radiative cooling materials.

[0033] Fifth, the production and preparation costs are low, and the difficulty of industrial-scale production is low. The main raw materials used in this invention are commercially available ultra-cold cement and conventional industrial alkali activators, with wide procurement channels and low overall procurement prices. The entire production and preparation process is simple to operate, requiring no investment in high-end precision production equipment. The overall process operating parameters are stable and easy to control, enabling rapid large-scale production.

[0034] Sixth, the product has strong adaptability and a wide range of downstream application scenarios. The high-whiteness cement-based radiative cooling filler prepared by this invention can be directly blended into various building energy-saving and industrial energy-saving cooling products such as radiative cooling coatings, building roof insulation powders, passive cooling mortars for large outdoor equipment, and photovoltaic backsheet heat dissipation and protection coatings, with broad market application prospects. Attached Figure Description

[0035] Figure 1 The solar reflectance spectrum of the ultracold cement-based porous radiation cooling packing prepared in Example 1 of this invention.

[0036] Figure 2 The images show the scanning electron microscope (SEM) microstructure of the radiation-cooling packings prepared in Examples 1 and 2 of this invention, revealing a hierarchical microporous structure uniformly distributed inside the packings. Detailed Implementation

[0037] The present invention will be further described in detail below with reference to specific embodiments and comparative examples, but the implementation of the present invention is not limited thereto. The raw materials used in the embodiments are all commercially available industrial products, and the operating methods involved are conventional operating methods in the art unless otherwise specified. Example 1

[0038] Raw material composition: The ultra-cold cement is made of white silicate cement with a specific surface area of ​​720 m². 2 / kg, iron oxide content is 0.15%wt, Hunter whiteness is 94.5. Sodium silicate is used as the alkali activator, and the addition amount is 4% of the mass of ultra-cold cement powder. The water-cement ratio of deionized water to cement is 3.0.

[0039] Preparation steps: (1) Raw material screening pretreatment: Select the above-mentioned ultra-cold cement and screen it using a 200-mesh standard inspection sieve to remove coarse agglomerated particles and hard inorganic impurities. After screening, seal it for later use.

[0040] (2) Dry powder uniform activation and compounding: The ultra-cold cement powder after sieving is put into the dry powder mixing equipment, and sodium silicate alkali activator is weighed at a ratio of 4% of the dry cement powder mass and added at the same time. The mixture is stirred at low speed for 8 minutes to complete the pre-activation treatment of composite cement powder.

[0041] (3) Preparation of ultra-high water-cement ratio flow dynamic cement paste: Pre-activated composite cement powder and room temperature deionized water are added to the high-strength stirring reaction equipment in sequence according to a water-cement ratio of 3.0. After the feeding is completed, the stirring is started immediately to carry out continuous stirring throughout the process, so that the cement paste always maintains a uniform flow suspension state.

[0042] (4) Constant temperature flow dynamic full hydration reaction: The entire stirring equipment is placed in a constant temperature curing environment of 30℃ and hydrated for 10 days under continuous stirring.

[0043] (5) Gradient segmented high temperature drying and shaping microporous structure: After the hydration is completed, the fluid dynamic cement slurry is left to stand to drain the surface free water, and then broken into small pieces; it is first pre-dried at a low temperature of 70℃ for 3 hours, and then heated to a high temperature of 180℃ for 8 hours.

[0044] (6) Ultrafine grinding and air classification purification: The dried material is fed into an ultrafine ball mill and ground to 1800 mesh, and then purified by an air classifier.

[0045] (7) Testing and Packaging: Test the various performance indicators of the finished product, and seal it in a moisture-proof manner after it meets the standards.

[0046] Testing revealed that the radiation-cooling packing material prepared in this embodiment has a Hunter whiteness of 96.4, an internal porosity of 48%, a loose bulk density of 275 kg / m³, a solar full-band reflectivity of 96.5%, and an emissivity of 0.96 in the 8–13 μm atmospheric window. Example 2

[0047] Raw material composition: The ultra-cold cement is made of white silicate cement with a specific surface area of ​​750 m². 2 / kg, iron oxide content is 0.12%wt, and Hunter whiteness is 95.0. Calcium hydroxide is used as the alkali activator, and the addition amount is 4% of the mass of the ultracold cement powder. The water-cement ratio of deionized water to cement is 4.0.

[0048] Preparation steps: (1) Raw material screening pretreatment: Same as step (1) in Example 1.

[0049] (2) Dry powder uniform activation and compounding: Weigh calcium hydroxide alkaline activator at a ratio of 4% of the dry cement powder mass, stir and mix at low speed for 6 minutes to complete the pre-activation treatment of composite cement powder.

[0050] (3) Preparation of ultra-high water-cement ratio dynamic cement paste: Deionized water is mixed according to a mass water-cement ratio of 4.0. After mixing, the paste is continuously stirred throughout the process to keep it in a flowing and suspended state.

[0051] (4) Constant temperature flow dynamic full hydration reaction: Under constant temperature of 35℃, continuously stir and hydrate for 12 days.

[0052] (5) Gradient segmented high temperature drying to shape microporous structure: pre-dry at 80℃ for 2 hours, then heat to 200℃ and dry at a constant temperature for 6 hours.

[0053] (6) Ultrafine grinding and air classification purification: After grinding to 2000 mesh, air classification purification is carried out.

[0054] (7) Packaging inspection: Same as step (7) in Example 1.

[0055] Testing revealed that the radiation-cooling packing material prepared in this embodiment has a Hunter whiteness of 97.3, an internal porosity of 53%, a loose bulk density of 260 kg / m³, a solar full-band reflectivity of 96.9%, and an emissivity of 0.96 in the 8–13 μm atmospheric window. Example 3

[0056] Raw material composition: The ultracold cement is made of white sulfoaluminate cement with a specific surface area of ​​780 m². 2 / kg, iron oxide content is 0.10%wt, and Hunter whiteness is 95.5. The alkali activator is a mixture of sodium silicate and calcium hydroxide in a 2:1 mass ratio, added at 4% of the mass of the ultra-cold cement dry powder. The water-cement ratio of deionized water to cement is 3.5.

[0057] Preparation steps: (1) Raw material screening pretreatment: Same as step (1) in Example 1.

[0058] (2) Dry powder uniform activation and compounding: Weigh the alkali activator at a ratio of 4% of the dry cement powder mass, stir and mix at low speed for 10 minutes to complete the pre-activation treatment of composite cement powder.

[0059] (3) Preparation of ultra-high water-cement ratio flow dynamic cement paste: Deionized water is prepared according to a mass water-cement ratio of 3.5, and the mixture is continuously stirred throughout the process after feeding.

[0060] (4) Constant temperature flow dynamic full hydration reaction: under constant temperature of 32℃, continuous stirring and hydration curing for 11 days.

[0061] (5) Gradient segmented high temperature drying to shape microporous structure: pre-dry at 75℃ for 3 hours, then heat up to 190℃ and dry at a constant temperature for 9 hours.

[0062] (6) Ultrafine grinding and air classification purification: After grinding to 1900 mesh, air classification purification is carried out.

[0063] (7) Packaging inspection: Same as step (7) in Example 1.

[0064] According to the test results, the radiation cooling packing prepared in this embodiment has a Hunter whiteness of 96.8, an internal porosity of 50%, a loose bulk density of 268 kg / m³, a solar full-band reflectivity of 96.7%, and an emissivity of 0.96 in the 8-13 μm atmospheric window. Example 4

[0065] Raw material composition: The ultracold cement used is the same white silicate cement as in Example 1, with a specific surface area of ​​720 m². 2 / kg, iron oxide content 0.15%wt, Hunter whiteness 94.5. Sodium silicate was used as the alkali activator, added at 2% of the mass of the ultracold cement powder. The water-cement ratio of deionized water to cement was 3.0. The preparation steps were exactly the same as in Example 1.

[0066] Testing revealed that the radiation-cooling packing material prepared in this embodiment had a Hunter whiteness of 95.6, an internal porosity of 42%, a loose bulk density of 285 kg / m³, a solar reflectance of 95.1% across the entire wavelength range, and an emissivity of 0.95 within the 8–13 μm atmospheric window. Compared to Example 1, both whiteness and reflectance showed a significant decrease, indicating insufficient activation when the amount of alkaline activator added was too low, inadequate dissolution of colored impurities, and impaired micropore development. Example 5

[0067] Raw material composition: The ultracold cement used is the same white silicate cement as in Example 1, with a specific surface area of ​​720 m². 2 / kg, iron oxide content 0.15%wt, Hunter whiteness 94.5. Sodium silicate was used as the alkali activator, added at 6% of the mass of the ultracold cement dry powder. The water-cement ratio of deionized water to cement was 3.0. The preparation steps were exactly the same as in Example 1.

[0068] Testing revealed that the radiative cooling packing material prepared in this embodiment had a Hunter whiteness of 96.0, an internal porosity of 46%, a loose bulk density of 278 kg / m³, a solar reflectance of 95.8% across the entire wavelength range, and an emissivity of 0.96 within the 8–13 μm atmospheric window. Although the whiteness and reflectance were improved compared to Example 4, they were still slightly lower than those of Example 1 (4% addition). This indicates that excessive alkali activator may introduce too many soluble salt residues, which could have a slight negative impact on whiteness.

[0069] Comparative Example 1 Select a specific surface area of ​​450 m² 2 Ordinary white cement of / kg was used to replace high specific surface area ultracold cement, and all other raw material composition and preparation process parameters were kept the same as in Example 1.

[0070] Testing revealed that the radiative cooling filler prepared in this comparative example had a Hunter whiteness of only 94.1, an internal porosity of only 27%, a loose bulk density of 320 kg / m³, a solar reflectance of only 93.5% across the entire wavelength range, and an emissivity of 0.94 within the 8–13 μm atmospheric window. Compared to Example 1, whiteness, porosity, and reflectance all decreased significantly. The results indicate that the low specific surface area cement raw material exhibits insufficient hydration reactivity, resulting in a low clinker mineral hydration conversion rate, which fails to adequately dissolve the chromogenic phase. Furthermore, insufficient hydration product formation leads to inadequate microporous structure development.

[0071] Comparative Example 2 The step of adding the alkali activator was omitted, and the composition of the remaining raw materials and the preparation process parameters remained the same as in Example 1.

[0072] Testing revealed that the radiative cooling filler prepared in this comparative example had a Hunter whiteness of 95.1, an internal porosity of 45%, a loose bulk density of 290 kg / m³, a solar reflectance of 94.7% across the entire wavelength range, and an emissivity of 0.96 within the 8–13 μm atmospheric window. Compared to Example 1, the whiteness and reflectance were significantly reduced, and the porosity also decreased slightly. This is because the cement hydration reaction rate was significantly slowed down without the addition of an alkali activator, resulting in insufficient dissolution and separation of colored impurities within the system, and sparse and uneven micropore development of the hydration products.

[0073] Comparative Example 3 During the cement hydration and curing stage, continuous mixing is stopped, allowing the slurry to stand naturally, solidify, and clump together. All other process parameters remain the same as in Example 1.

[0074] Testing revealed that the radiative cooling packing prepared in this comparative example had a Hunter whiteness of 94.3, an internal porosity of only 22%, a loose bulk density of 360 kg / m³, a solar reflectance of 93.9% across the entire wavelength range, and an emissivity of 0.95 within the 8–13 μm atmospheric window. Compared to Example 1, the porosity was significantly reduced, and the whiteness and reflectance were also markedly decreased. This is because during the static solidification process, the formed pores within the system experienced large-area compaction and collapse due to solid-phase compression, leading to the destruction of the microporous structure.

[0075] Comparative Example 4 The slurry was prepared using a standard low water-cement ratio of 0.5, and the remaining process parameters were the same as in Example 1.

[0076] Testing revealed that the radiative cooling packing material prepared in this comparative example had a Hunter whiteness of only 92.3, an internal porosity of only 15%, a loose bulk density as high as 420 kg / m³, a solar reflectivity of only 91.2% across the entire wavelength range, and an emissivity of only 0.92 within the 8–13 μm atmospheric window. Due to the lack of in-situ pore-forming conditions with an ultra-high water-cement ratio of 3.0–4.0, the prepared material exhibited a dense and compact overall structure, failing to form a multi-level microporous structure. Consequently, the overall radiative cooling performance of the product was significantly lower than that of the product prepared using the technical solution of this invention.

[0077] Comparative Example 5 After hydration, the product is dried at a low temperature of 70°C, without the high-temperature deep drying step of 150-200°C. The remaining process parameters are the same as in Example 1.

[0078] Testing revealed that the radiation-cooling filler prepared in this comparative example had a Hunter whiteness of 95.0, an internal porosity of 47%, a loose bulk density of 278 kg / m³, a solar reflectance of 95.3% across the entire wavelength range, and an emissivity of 0.95 within the 8–13 μm atmospheric window. Compared to Example 1, while the porosity was similar, the whiteness and reflectance were significantly lower. This is because the filler underwent high-temperature deep drying treatment, resulting in the failure to eliminate hydroxide vacancies and low-valence iron ion lattice color center defects within the hydration product crystal lattice. The residual slightly yellow and slightly gray undertones of the powder further hindered whiteness improvement.

[0079] Comparative Example 6 The temperature for the high-temperature deep drying stage was set at 120℃ (lower than the lower limit of 150℃ in this invention), and the drying was carried out at a constant temperature for 8 hours. The remaining process parameters were the same as in Example 1.

[0080] Testing revealed that the radiation-cooled filler prepared in this comparative example had a Hunter whiteness of 95.4, an internal porosity of 47%, a loose bulk density of 276 kg / m³, a solar reflectance of 95.6% across the entire wavelength range, and an emissivity of 0.95 within the 8–13 μm atmospheric window. Compared to Example 1, the drying temperature of 120°C was lower than the 150–200°C range specified in this invention. Although the porosity difference was not significant, the whiteness and reflectance could not reach the level of Example 1. This indicates that a drying temperature that is too low is insufficient to completely eliminate lattice color center defects.

[0081] Performance Summary Analysis Figure 1 The image shows the solar reflectance spectrum of the radiation-cooling packing material prepared in Example 1 of this invention. Figure 1 It can be seen that the reflectivity of the filler is higher than 96% in the entire solar spectrum (0.25-2.5μm), indicating that it has excellent solar reflectivity.

[0082] Figure 2These are scanning electron microscope (SEM) microstructure images of the radiation-cooling packings prepared in Examples 1 and 2 of this invention. Figure 2 It can be clearly seen that the packing material contains a uniformly distributed hierarchical microporous structure ranging from 20 to 500 nm. The pores are well-developed, uniformly distributed, and without large dense areas. This microstructural characteristic is consistent with the porosity data of Examples 1 and 2 in Table 1 (48% and 53%, respectively), confirming that the ultra-high water-cement ratio combined with the full-process dynamic stirring process of this invention can effectively construct a regular multi-level microporous structure, thus providing a sufficient microstructural basis for Mie scattering and Rayleigh scattering of visible light.

[0083] The key performance indicators of the above embodiments and comparative examples are summarized, and the results are shown in Table 1.

[0084] Table 1 Summary of performance indicators for each embodiment and comparative example

[0085] As shown in Table 1, Examples 1-3 all meet the performance indicators of this invention: Hunter whiteness ≥ 96, porosity 40%-60%, solar reflectance ≥ 96%, and atmospheric window emissivity ≥ 0.95. However, Comparative Example 1, using ordinary cement with a low specific surface area, suffers from insufficient hydration activity, resulting in a porosity of only 27%, and both whiteness and reflectance fail to meet the standards. Comparative Example 2, without the alkali activator, exhibits significantly lower whiteness and reflectance than Example 1 due to a slow hydration reaction rate and insufficient dissolution of colored impurities, indicating that the alkali activator has an irreplaceable synergistic activation and impurity removal modification effect. Comparative Example 3, by eliminating full-process stirring and allowing the slurry to settle... The porosity of Example 1 was reduced to only 22% due to solidification and collapse caused by solid-phase compression, indicating that dynamic stirring throughout the process has a significant impact on maintaining the integrity of the pore structure. Comparative Example 4, using a conventional low water-cement ratio, had a porosity of only 15% and a dense structure due to the lack of an in-situ pore-forming water template. Comparative Example 5 only underwent low-temperature drying without high-temperature deep drying, resulting in a whiteness of only 95.0 due to the failure to eliminate lattice color center defects, demonstrating the irreplaceable role of high-temperature deep drying in eliminating color center defects and improving whiteness. Comparative Example 6, with a high-temperature drying temperature of only 120℃ (below the lower limit of 150℃), had whiteness and reflectivity lower than Example 1. This invention utilizes high specific surface area ultra-cold cement raw materials, alkali activator activation, ultra-high water-cement ratio, dynamic stirring hydration throughout the process, and high-temperature deep drying at 150–200℃, which have a synergistic effect, to prepare high-performance radiative cooling fillers.

[0086] The radiation-cooling filler prepared in Example 1 of this invention was incorporated into a water-based acrylic coating at a mass ratio of 20% and coated onto the surface of an aluminum plate to form a 200 μm dry film thickness coating. Under outdoor direct sunlight conditions (ambient temperature 35℃, irradiance of about 850 W / m²), the measured surface temperature of the coating was 4.2℃ lower than that of the control coating containing the same proportion of rutile titanium dioxide and 12.5℃ lower than that of the blank aluminum plate.

[0087] The filler prepared in Example 1 of this invention was subjected to a QUV accelerated aging test (UVA-340 lamp, irradiance 0.89 W / m² / nm, alternating cycles of 4h illumination at 60℃ and 4h condensation at 50℃) for 1000h. The Hunter whiteness decreased only 0.5 from the initial 96.4 to 95.9, and the solar reflectance decreased only 0.5 percentage points from 96.5% to 96.0%. Under the same testing conditions, the Hunter whiteness of commercially available rutile titanium dioxide decreased from 95.2 to 92.8, a decrease of 2.4, and the reflectance decreased from 95.8% to 93.2%, a decrease of 2.6 percentage points. The results indicate that the all-inorganic cement-based filler prepared in this invention exhibits significantly better weather resistance stability under ultraviolet light and humid heat conditions than traditional titanium dioxide fillers.

[0088] The specific surface area of ​​the packing material in Example 1 was tested using the BET nitrogen adsorption method and found to be 38.6 m² / g. The most probable pore size was calculated to be 45 nm using the BJH model. The pore size was concentrated in the range of 18–480 nm, which has a good scattering matching relationship with the visible light wavelength (380–780 nm).

[0089] The ultracold cement-based porous radiative cooling filler and its preparation method provided by this invention have widely available and low-cost raw materials, and the preparation process is simple and controllable, requiring no complex equipment, making it suitable for large-scale industrial production. The obtained radiative cooling filler can be directly incorporated as a functional component into products such as radiative cooling coatings, building roof insulation powders, passive cooling mortars for large outdoor equipment, and photovoltaic backsheet heat dissipation and protective coatings, showing broad application prospects in building energy conservation, passive cooling of outdoor equipment, and urban heat island management.

[0090] The above description is only a preferred embodiment of the present invention. It should be noted that for those skilled in the art, several improvements and modifications can be made without departing from the principle of the present invention, and these improvements and modifications should also be considered within the scope of protection of the present invention.

Claims

1. A type of ultracold cement-based porous radiation cooling packing, characterized in that, It is prepared from ultracold cement, alkali activator and water, wherein the powder specific surface area of ​​the ultracold cement is ≥700m². 2 / kg, Hunter whiteness > 94 degrees, iron oxide content ≤ 0.2%wt, the amount of alkali activator added is 2% to 6% of the total mass of the ultracold cement dry powder, and the water-cement ratio of the water to the ultracold cement is 3.0 to 4.

0.

2. The ultracold cement-based porous radiative cooling packing material according to claim 1, characterized in that, The amount of alkali activator added is 4% of the total mass of the ultracold cement dry powder.

3. The ultracold cement-based porous radiation cooling packing material according to claim 1, characterized in that, The ultracold cement is white silicate cement or white sulfoaluminate cement, with a specific surface area of ​​700–900 m². 2 / kg, Hunter Whiteness is 94-97 degrees.

4. The ultracold cement-based porous radiation cooling packing material according to claim 1, characterized in that, The alkaline activator is selected from any one of sodium silicate, calcium hydroxide, and potassium hydroxide, or a compound mixture of the above components.

5. The ultracold cement-based porous radiative cooling packing material according to claim 4, characterized in that, The alkaline activator is a mixture of sodium silicate and calcium hydroxide in a mass ratio of (1-3):

1.

6. The ultracold cement-based porous radiation cooling packing material according to claim 1, characterized in that, The water-cement ratio is 3.2 to 3.

8.

7. A method for preparing an ultracold cement-based porous radiation cooling packing, characterized in that, Includes the following steps: Step 1: Raw material screening and pretreatment: Select raw materials with a specific surface area ≥700 m² 2 Ultra-cold cement with a weight of / kg, Hunter whiteness >94 degrees, and iron oxide content ≤0.2% is screened and then sealed for later use. Step 2: Uniform activation and compounding of dry powder: The sieved ultracold cement powder is put into the dry powder mixing equipment. The alkali activator is weighed at a ratio of 2% to 6% of the total mass of the ultracold cement dry powder and added at the same time. The mixture is stirred to complete the pre-activation treatment of the composite cement powder. Step 3: Preparation of ultra-high water-cement ratio flow dynamic cement slurry: According to the mass water-cement ratio of 3.0 to 4.0, the pre-activated composite cement powder and room temperature water are added to the mixing and reaction equipment in sequence. After the feeding is completed, the mixing equipment is turned on to carry out continuous mixing operation throughout the process, so that the mixed cement slurry always maintains a uniform flow suspension state. Step 4: Constant temperature and dynamic hydration reaction: Place the mixing equipment containing the dynamic cement slurry in a constant temperature curing environment of 25-40℃ and maintain constant temperature hydration curing for 7-14 days under continuous mixing. Step 5: Gradient-segmented high-temperature drying and shaping of microporous structure: After the hydration reaction, the fluid cement slurry is left to stand to drain the surface free water, broken into small pieces, pre-dried at a low temperature of 60-80℃ for 2-4 hours, and then heated to a high temperature of 150-200℃ for 6-12 hours for deep drying. Step 6, Ultrafine grinding and air classification purification: The dried hydrated solid material is fed into an ultrafine ball mill for grinding, and then screened and purified using an air classifier; Step 7: Testing and Packaging: Test the performance indicators of the finished product, and package and put it into storage after it meets the standards.

8. The preparation method of the ultracold cement-based porous radiation cooling packing according to claim 7, characterized in that, The constant temperature curing temperature in step four is 30-35℃, and the hydration curing time is 10-12 days.

9. The preparation method of the ultracold cement-based porous radiation cooling packing according to claim 7, characterized in that, The high-temperature deep drying temperature mentioned in step five is 180-200℃.

10. The preparation method of the ultracold cement-based porous radiation cooling packing according to claim 7, characterized in that, The grinding particle size in step six is ​​controlled at 1800-2000 mesh.

Citation Information

Patent Citations

  • Radiation refrigeration cement-based material with metasurface as well as preparation method and application of radiation refrigeration cement-based material

    CN120004577A

  • Porous microstructure foaming white cement radiation refrigeration composite material and preparation method thereof

    CN121990801A